Javanese Phrase Construction in Classical Books Translation - Masrukhi, Moh. (Register Journal, 2010)
When the system or structure of language is used and influenced by other languages, it is called interference, and it may ruin the concept of structures.Â Â  This research is about Arabic phrase construction that influenced Javanese phrase construction in classical books translation (TKK). This involvement appears when the concept of Arabicâs construction is translated literally into Javanese.Â Â  The research was carried out by applying theories of interference and translation. Itâs analysis approach with contrastive analysis which is allegedly enabled errors to be predicted from a comparison between Arabicâs and Javaneseâs phrase construction. The data were found and collected from several classical books in Arabic language (KKbA) translated by different writers. The results show that Javanese phrase construction (as the target language), particularly, with noun phrases,Â  with adjectival phrases, with numeral phrases, and with prepositional phrases was influenced by Arabicâs murakkab or Arabic phrase construction (as the source language). Arabic has its own concept of phrase construction.Â  The phrase construction cannot be translated into Javanese directly through word-for-word translation or literal translation. Thus, Javanese in TKK became inconvenient and ungrammatical. Arabic phrase construction is flipped around (with noun phrases and adjectival phrases) and prepositions are used and translated improperly or in the wrong position (with prepositional phrases). This research has many implications for further use, such as: for the identification and description of the deviation ofÂ  Javanese phrase construction which has been affected by direct translation from the Arabic language,Â  and furthermore, to increase the knowledge of those who are learning by increasing the realization and awareness in writing and translating (especially from Arabic to Javanese) about the fact thatÂ  Arabic and JavaneseÂ  have their own regulations or patterns which areÂ  differentÂ  then the other language.Â Â keywords;Influence; Literal Translation; Phrase Construction ; Murakkab